2009
DOI: 10.2516/ogst/2009034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Butanol–Gasoline Blends in a Port Fuel-injection, Spark-Ignition Engine

Abstract: Résumé -Évaluation de mélange butanol-essence dans un moteur à allumage commandé à injection indirecte -Cet article évalue le potentiel de l'utilisation de différents mélanges butanolessence dans un moteur à allumage commandé à injection indirecte afin de quantifier l'influence de l'ajout de butanol sur les émissions des hydrocarbures imbrûlés (HC), le monoxyde de carbone (CO) et les oxydes d'azote (NOx). De plus, l'influence sur la stabilité de combustion, le délai d'inflammation et sur la durée de la phase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
88
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(109 citation statements)
references
References 19 publications
(54 reference statements)
18
88
3
Order By: Relevance
“…Lower NO x emissions when using the alcohol are in line with the findings of most studies about butanol combustion in SI engines [14]- [16].The reduction in NOx emissions is due to the low adiabatic temperature when engine operates on butanol. …”
Section: A Thermodynamic Analysissupporting
confidence: 77%
“…Lower NO x emissions when using the alcohol are in line with the findings of most studies about butanol combustion in SI engines [14]- [16].The reduction in NOx emissions is due to the low adiabatic temperature when engine operates on butanol. …”
Section: A Thermodynamic Analysissupporting
confidence: 77%
“…Butanol itself has been studied in the literature much less than ethanol and mostly in PFI engines as well; some benefits in terms of blending have been reported (e.g. better stability) but trends have been sensitive to equivalence ratio, spark timing, engine temperature and valve overlap (Malcolm et al, 2007;Todd et al, 2010;Szwaja and Naber, 2010;Dernotte et al, 2010;Merola et al, 2011Merola et al, , 2012Tornatore et al, 2013;Cairns et al, 2013;Deng et al, 2013;Brequigny et al, 2013). In contrast, very few alcohol-blended combustion studies have been conducted in latest technology Direct Injection Spark-Ignition (DISI) engines that are more sensitive to fuel properties than PFI engines.…”
Section: Combustion Of Alcohol Fuel Blends In Enginesmentioning
confidence: 99%
“…By analysing the heat release of butanol/gasoline blends (hereafter called butanol blends), Yang et al [6] found that, without any modifications to the original engine, the ignition delay of butanol blends is longer than that of gasoline, while the peak value of IHRR of butanol blends is smaller. What's more, literatures [7][8][9] discovered that when the blend ratio of butanol is less than 20%, the engine power remains about the same, while CO and NO X emissions decrease.…”
Section: Introductionmentioning
confidence: 99%